PEMAKNAAN FISABILILLAH UNTUK PETUGAS KEAMANAN (SATPAM) SEBAGAI MUSTAHIK ZAKAT DI PERUMAHAN TAMAN PONDOK JATI SIDOARJO - Abdul Rozak (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2016)
The results showed that some religious leaders in Taman Pondok Jati looked fi sabilillah with common meanings and wider, which includes all things that are in the common interest of the Muslims, a security guard holding a mandate as guardians of the security and comfort of the Muslims for 24 hours, so that from the sense of security that people can worship in peace and teachings of other religion can also be implemented. As for the meaning of fi sabilillah for security officers (guards) as mustahik zakat in Taman Pondok Jati in accordance with the meaning fi sabilillah into the general meaning, as explained by the scholars' contemporary, that all matters relating to the welfare of the Muslims who tend to be aimed at obtaining contentment of Allah SWT. In addition, the actual security guard can also be classified into poor, when viewed from the side of a relatively small income.